Lightweight authentication scheme for smart grid using Merkle hash tree and lossless compression hybrid method - Tohidi, Hamed; Vakili, Vahid Tabataba (IET communications, 2018)
In order to make efficient use of the benefits of smart grid, meeting the security objectives of the network seems an essential requirement. Implementation of authentication protocols on the communication among the nodes of the network plays an important role in achieving the security objectives. In this study, a lightweight authentication scheme is presented for the connection between the neighbourhood area network gateway and the control centre in the smart grid. In the proposed scheme, a lossless compression algorithm, as well as Merkel hash tree, is used to compress the data prior to cryptography. Due to the fact that large amounts of data are compressed in the compression process and then Merkel tree is applied on them, confidentiality of the data against cryptanalysis attacks has increased considerably. Security analysis of the proposed scheme indicates that the objectives of confidentiality, data integrity, and availability have been fully achieved, and the process of authentication and counteraction to the replay attack has been successfully applied. In addition, making use of the compression algorithm, as well as one time pad cryptography system, tends to reduce the computational, communication, and storage costs of the proposed scheme compared to previous scheme.